Typological characterization and temporality of the stubble agroecosystem in Chiapas, Mexico - Gómez-Padilla, Ernesto Javier (2026)
Introduction. Maize stubble plays a fundamental role in the productive dynamics of the Frailesca region, Chiapas, Mexico, by linking agricultural and livestock agroecosystems and ensuring the subsistence of producers during drought periods. Objective. To characterize and typify the stubble-based agroecosystem of the Frailesca region, based on the seasonality of the dry period, the maize production cycle, and the different uses of stubble. Materials and methods. Semi-structured interviews were conducted, and production records were collected from sixty producers between January and December 2023 in the municipalities of Villa Corzo, Villaflores, and La Concordia in the Frailesca region, Chiapas, Mexico, using snowball sampling. For the characterization, variables related to context, area, land tenure, and the stubble, maize, and livestock agroecosystems were included. Typological variants of seasonality and systemic management were determined. Groups were defined through factorial and cluster analyses, and the association between typologies was assessed through correspondence factorial analysis. Results. The seasonality typology grouped producers into three categories: (1) those who perceive the maize cycle as late and short; (2) those who perceive it as early and long; and (3) those who perceive the dry period as late and short. In all groups, stubble perception was similar. Regarding management practices, three groups were identified: (1) livestock farmers with access to technology; (2) livestock farmers with limited resources; and (3) maize farmers who commercialize stubble. Conclusions. The stubble-based agroecosystem is organized into three temporal dimensions that influence management strategies. Differentiated management forms were identified, which present distinct adaptations according to access to resources and demonstrate the relevance of seasonality for sustainability.